Extrapleural solitary fibrous tumor—a revision of three cases. Issue 3 (28th March 2023) - Policarpo, Filipa; Rafael, Ana Alves; Teixeira, José Nuno; Chorão, Martinha
ABSTRACT: Extrapleural solitary fibrous tumors are a rare type of spindle cell neoplasm, which can occur in many locations with different histologic and immunohistochemical findings, making the diagnosis challenging. They are usually indolent and their treatment is based on complete surgical resection. There are still some issues to be clarified regarding systemic therapy (specifically when aggressive behavior exists) and long-term follow-up. We present a series of clinical cases in the same Department and review this thematic area.